2005
DOI: 10.1177/1069072705274960
|View full text |Cite
|
Sign up to set email alerts
|

Examining Contextual Factors in the Career Decision Status of African American Adolescents

Abstract: This study examined the extent to which perceived occupational barriers and perceived parental support predicted career certainty and career indecision in a sample of African American adolescents. Perceived occupational barriers were positively predictive of career indecision, and perceived parental support was positively associated with career certainty. The results provided support for the importance of considering contextual variables, such as perceived occupational barriers and perceived parental support, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
0
8

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 97 publications
(99 citation statements)
references
References 40 publications
(78 reference statements)
5
86
0
8
Order By: Relevance
“…For example, adolescents who perceived their teachers to be supportive, had more confidence in their career decision-making ability (Metheny, McWhirter, & O'Neil, 2008). A lack of perceived support from either teachers or parents, on the other hand, resulted in adolescents feeling uncertainty about their careers (Constantine, Wallace, & Kindaichi, 2005;Metheny, McWhirter, & O'Neil, 2008). Family and monetary support predicted happiness in a sample of married adults (North, Holahan, Moos, & Cronkite, 2008), while Lett and colleagues (2005) examined functional support in a group of patients with heart disease and found that low levels of support resulted in a 1.5 to 2.0 fold increased risk for mortality and morbidity.…”
Section: Sources Of Supportmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, adolescents who perceived their teachers to be supportive, had more confidence in their career decision-making ability (Metheny, McWhirter, & O'Neil, 2008). A lack of perceived support from either teachers or parents, on the other hand, resulted in adolescents feeling uncertainty about their careers (Constantine, Wallace, & Kindaichi, 2005;Metheny, McWhirter, & O'Neil, 2008). Family and monetary support predicted happiness in a sample of married adults (North, Holahan, Moos, & Cronkite, 2008), while Lett and colleagues (2005) examined functional support in a group of patients with heart disease and found that low levels of support resulted in a 1.5 to 2.0 fold increased risk for mortality and morbidity.…”
Section: Sources Of Supportmentioning
confidence: 99%
“…The previously mentioned research indeed point to the importance of social support as predictors of health and well-being but also looks at these sources from a singular perspective. Constantine et al (2005), Metheny et al (2008), North et al (2008) and others' work tells us that social support networks and systems are important but, having multiple sources of social support may be more beneficial than singular sources of social support. This underscores the need for additional research that looks at an additive model of social support networks and systems on psychological well-being.…”
Section: Summary and Current Studymentioning
confidence: 99%
“…Most researchers and practitioners have long recognized the impact of parents in the career planning process (Gottfredson, 1981;Hartung, Portfeli, & Vondraek, 2005;Lent, Brown, and Hackett, 1994;Super, Savickas, & Super, 1991;Whiston & Keller, 2004). However much of the current knowledge of parental influence is primarily based on what is known about Caucasian American populations (Flores & Ali, 2004), despite research that indicates that the influence of parents on the career development process may differ for racial ethnic minorities (Constantine, Wallace, & Kindaichi, 2005;Tang, 2002). Therefore this section will further explore the literature that examines the familial influences on the career development specific to Asian…”
Section: Familial and Individual Factorsmentioning
confidence: 99%
“…D'autres études (Samson et Gazzola, 2007;Germeijs et Verschueren, 2007;Guichard, 2001;Ireh, 2000) ont montré le rôle et l'importance de l'éducation à la carrière et de l'orientation professionnelle dans le développement des stratégies nécessaires pour assurer la transition de l'école vers le marché de l'emploi. L'incompréhension des barrières professionnelles et les biais des sources d'information consultées par les jeunes, que ce soit les parents, l'école, les amis ou les médias, constituent selon plusieurs chercheurs (Hargrove, Inman, et Crane, 2005;Constantine, Wallace et Kindaichi, 2005) des facteurs de l'indécision professionnelle.…”
Section: Les Jeunes Francophones Face Au Monde Du Travailunclassified